2010
DOI: 10.1007/s11596-010-0654-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical classification and treatment strategy of hamate hook fracture

Abstract: To explore the clinical classification of hamate hook fracture and the treatment strategy for different type of fractures, 12 patients who suffered from hamate hook fractures were followed up retrospectively. According to the fracture sites and the prognosis, we classified the hamate hook fractures into 3 types. Type I referred to an avulsion fracture at the tip of hamate hook, type II was a fracture in the middle part of hamate hook, and type III represented a fracture at the base of hamate hook. By the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 12 publications
(11 reference statements)
0
31
1
Order By: Relevance
“…Xiong et al classified hamate hook fractures on the basis of the fracture sites into 3 types: Type I referred to an avulsion fracture at the tip of hamate hook, type II was a fracture in the middle part of the hamate hook, and type III represented a fracture at the base of the hamate hook. In their study type II was the commonest fracture 15 . The weakest part of the hamate hook defined in the present study also lies in the middle part of the hamate hook.…”
Section: Discussionmentioning
confidence: 90%
“…Xiong et al classified hamate hook fractures on the basis of the fracture sites into 3 types: Type I referred to an avulsion fracture at the tip of hamate hook, type II was a fracture in the middle part of the hamate hook, and type III represented a fracture at the base of the hamate hook. In their study type II was the commonest fracture 15 . The weakest part of the hamate hook defined in the present study also lies in the middle part of the hamate hook.…”
Section: Discussionmentioning
confidence: 90%
“…Consolidation of the fracture site should be ensured and documented by CT, as small finger tendons can be frayed by the fracture site, which could ultimately lead to a rupture of the tendon. 3,6 Furthermore, the ulnar nerve can be irritated by loose fragments. 3,6,9,12,18 Of the 3 options for treating hamate hook fractures (excision of the fragments, open reduction and internal fixation, and cast immobilization), most reports indicate a preference for excision of the fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we recommend conservative therapy or open reduction and internal fixation to avoid fragment resection in type I fractures, especially in type I(II) or type I(III) cases in which relatively large fragments have been detected via CT. Xiong et al reported a high risk of nonunions, especially in type I (II) fractures with fracture sites in the center of the hook. 3 However, even patients with conservatively treated type I(II) fractures mostly experienced good healing. Nevertheless, physicians should be cognizant of the risk of nonunions; in such cases, a resection of the fragments and the residual base of the hook combined with a coverage of the fracture section with soft tissue is required.…”
Section: Discussionmentioning
confidence: 99%
“…Fractures involving the hook are the most common type of hamate fracture [2]. The incidence of hook of the hamate fractures among professional and recreational athletes is much higher than in the general population and is posited to be on the rise owing to the increasing popularity of golf and racket sports [9, 12]. Several mechanisms cause hook of the hamate fractures, including blunt trauma, repetitive microtrauma, and avulsion injury.…”
Section: Hook Of the Hamate Fracturesmentioning
confidence: 99%
“…4 and 5). Type 3 fractures account for over 75% of hook of the hamate fractures [4, 12]. Acute traumatic fractures of the hook often present with other fractures of the distal upper extremity, especially distal radial fractures [14] (Fig.…”
Section: Hook Of the Hamate Fracturesmentioning
confidence: 99%